Latent class analysis of substance use among men who have sex with men in Malaysia: Findings from the Asian Internet MSM Sex Survey. (1st June 2015) - Lim, Sin How; Cheung, Doug H.; Guadamuz, Thomas E.; Wei, Chongyi; Koe, Stuart; Altice, Frederick L.
Highlights: There appear to be three typologies (or latent classes) of substance use among men who have sex with men (MSM) in Malaysia. The majority of participants were negligible or non-drug users. A small group of MSM used amyl nitrates and ecstasy. A small group of MSM were stimulant users, mostly amphetamine-type substances (ATS), which was independently associated with being HIV-infected and other HIV-related transmission behaviors. Abstract: Background: High prevalence of substance use among men who have sex with men (MSM) may drive the HIV epidemic in Malaysia but patterns of substance use among Malaysian MSM have not been examined. Our study investigated specific Malaysian MSM risk groups to determine the association between their substance use and sexual risk behaviors. Methods: Data from Malaysian respondents ( n  = 1235) in a large, multinational online survey of Asian MSM in 2010 were used to identify latent classes of substance use. Subsequent covariates were included in a joint model to predict class membership. Results: The 3-class model was identified as the best fitting model, which included: (1) 'negligible substance use' for those reporting none or using any substance sparingly; (2) 'soft substance use' for those using poppers, ecstasy and drinking before sex; and (3) 'amphetamine-type stimulant (ATS) use' for those using stimulants (methamphetamine, ecstasy), erectile dysfunction drugs and recreational drug use before sex. Men in the 'ATS use' category were significantly less likely to not know their HIV status (AOR: 0.30, 95%CI: 0.14, 0.66), more likely to have had more than 6 male sex partners (AOR: 4.83, 95% CI: 1.92–12.2), to have group sex (AOR:4.07, 95% CI: 2.31–7.15), to report inconsistent condom use (AOR:2.01, 95% CI: 1.12–3.60), to be HIV-infected (AOR:3.92, 95% CI: 1.63–8.42) and to have had any sexually transmitted infections (AOR:3.92, 95% CI:1.70, 9.08), compared to men in the 'negligible substance use' category. Conclusions: Our study identified subgroups of Malaysian MSM with distinct substance use patterns and HIV-related risk profiles, which provides implication for targeting HIV prevention in this subpopulation.